Studi Analisis Metode Kias antara Mengusap Jaurab dengan Mengusap Khuf Perspektif Fikih Ibadah - Akhmad Hanafi Dain Yunta; Abdul Munawir; Iyadh Nazih (AL-QIBLAH: Jurnal Studi Islam dan Bahasa Arab, 2023)
This research aims to analyze the method of analogy between wiping over socks and wiping over leather footwear (khuf) from the perspective of Islamic jurisprudence (fiqh of worship). This study falls into the category of qualitative research using the library research method, which involves collecting data from books and previous literature or gathering data from other writings and sources, whether from scientific articles, primary data sources, secondary data sources, and other literature related to the method of analogy. The findings of the research are as follows: First, the type of analogy used in determining the ruling of wiping over socks by analogy with the ruling of wiping over leather footwear is 'illah analogy, by equating the effective cause (illat) of the subsidiary ruling with the original ruling, where the determination of the effective cause is done using the istinbat method through munasabah (suitability). Second, the analogy method used to determine the permissibility of wiping over socks in ablution as a substitute for washing the feet, by analogy with the ruling of wiping over leather footwear, is valid because it fulfills the pillars of analogy and also meets the conditions of each pillar.